(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to analyze visitor motivations and satisfaction with the Ajloun cable car experience, identify the spatial and service characteristics affecting the quality of the tourist experience, and measure the overall level of satisfaction. The study employed a descriptive-analytical approach, relying on a field questionnaire distributed to a sample of Ajloun cable car visitors during the peak tourist season. Data were analyzed using descriptive statistical methods. The results showed that the majority of visitors were domestic tourists, and that the site’s aesthetic appeal was the most prominent factor attracting them, with the beauty of the natural scenery receiving the highest rating. The overall level of satisfaction with the services and spatial features was also found to be high, although some facilities, such as seating areas and restrooms, were identified as needing improvement. Furthermore, the results indicated that a significant percentage of visitors expressed a desire to repeat their visit and recommend the site to others, reflecting the project’s success in promoting mountain tourism and enhancing the visitor experience in Jordan.